The relationship between quality of life assessed by go-qol and clinical activities score in patients with thyroid eye disease in the integrated oncology eye clinic of Dr. Soetomo General hospital, Indonesia: A literature review - Pramono, Amanda Cesariani; Fatmariyanti, Susy; Primitasari, Yulia (Edelweiss Applied Science and Technology, 2024)
Managing thyroid eye disease (TED) is challenging because of its complexity and diverse clinical manifestations. TED treatment strategies are tailored to disease severity, ranging from conservative options, such as artificial tears and prism glasses for mild cases, to more aggressive treatments, including intravenous methylprednisolone and orbital decompression, for moderate to severe cases with potential vision loss. TED can significantly impact patients’ quality of life and psychological well-being, particularly through changes in visual acuity and facial aesthetics. Various sequelae of TED, such as eye discomfort, diplopia, keratitis, and visual impairment, can negatively impact quality of life, emphasizing the necessity for comprehensive management strategies. Assessments of quality of life using tools such as the Graves’ Ophthalmopathy Quality of Life (GO-QoL) questionnaire underscore the substantial effects of TED on patients’ physical and mental well-being. Further research is essential to understand the link between clinical activity scores and quality of life in TED patients. This review seeks to address the literature gap and enhance comprehensive care for these patients.